The impact of emotional intelligence skills to entrepreneurial business success - Natasha Ristovska; Daliborka Blazheska (UTMS Journal of Economics, 2021)
Business leaders are playing entrepreneurial roles in the process of decision making. As entrepreneurs, they are characterized with high level of creativity, innovation, taking chances and risks but also their high emotional intelligence can be extremely beneficial. These EQ skills give them better understanding of the needs, feelings, and overall situation of others. Therefore, entrepreneurs with high emotional intelligence can effectively create a product or service to fit the needs and expectations of their target customers, and business leaders with high emotional intelligence can create quality interpersonal relationships and enhance employees' motivation. As a result, business success can be achieved, operating performance can increase, as well as the overall business effectiveness and efficiency. The purpose of this paper is to elaborate the influence of EQ skills on business leaders and entrepreneurial success. The analysis is focused on the connection between emotional intelligence and intellectual intelligence, models and components of emotional intelligence, dimensions and factors of emotional intelligence. The importance of assessing, developing and upgrading the emotional skills is also highlighted. Secondary research is provided and supported by survey conducted in North Macedonia on representative number of 30 entrepreneurs in order to determine their awareness for EQ, the usage of EQ skills, and the importance of enhancing EQ skills for business success.
Keywords: M13; L26; 330; entrepreneurship; business; emotional intelligence; EQ skills